ANALISIS PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) GURU DALAM PEMBELAJARAN DI SDN 2 TAHUNAN JEPARA - Henny Lestari; Naili Rofiqoh; Aan Widiyono (Journal of Professional Elementary Education, 2022)
This study aims to: (1) to analyze the Utilization of Information and Communication Technology (ICT) Teachers in Learning at SDN 2 Tahunana Jepara; and (2) To analyze the supporting factors and inhibiting factors for the Utilization of Information and Communication Technology (ICT) Teachers in Learning at SDN 2 Tahunana Jepara. This research uses a qualitative approach with descriptive research type. Data collected through data collection techniques in the form of observation, interviews and documentation. The results of this study indicate that the use of information and communication technology (ICT) teachers in learning at SDN 2 Tahunan Jepara through WhatsApp Group, Youtube and Zoom Meeting. The use of ICT in SDN 2 Tahun Jepara is still very rare. Because, the facilities and infrastructure are still lacking, the knowledge of teachers in technology is still lacking and there is very little time to make learning media using technology. Supporting factors include: teachers are easier to convey material to students, students are more interested in learning and students are easier to understand the material presented by the teacher. While the inhibiting factors include: lack of infrastructure and technological facilities for learning in the classroom, teacher knowledge of technology and lack of time